2014
DOI: 10.1177/0959683614534741
|View full text |Cite
|
Sign up to set email alerts
|

Climatic imprint of the mid-latitude Westerlies in the Central Tian Shan of Kyrgyzstan and teleconnections to North Atlantic climate variability during the last 6000 years

Abstract: In general, a moderate drying trend is observed in mid-latitude arid Central Asia since the Mid-Holocene, attributed to the progressively weakening influence of the mid-latitude Westerlies on regional climate. However, as the spatio-temporal pattern of this development and the underlying climatic mechanisms are yet not fully understood, new high-resolution paleoclimate records from this region are needed. Within this study, a sediment core from Lake Son Kol (Central Kyrgyzstan) was investigated using sedimento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
87
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 77 publications
6
87
0
Order By: Relevance
“…the lake from the north-east. The present-day regional climate is temperate continental (Wang et al, 2017) and dominated by the interaction between the Siberian anticyclonic circulation and the mid-latitude Westerlies (Aizen et al, 1997;Lauterbach et al, 2014). Owing to the high mountain ranges of the Tian Shan that prevent the transport of moisture, rainfall is reduced, especially in January and February (Aizen et al, 1995(Aizen et al, , 2001.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…the lake from the north-east. The present-day regional climate is temperate continental (Wang et al, 2017) and dominated by the interaction between the Siberian anticyclonic circulation and the mid-latitude Westerlies (Aizen et al, 1997;Lauterbach et al, 2014). Owing to the high mountain ranges of the Tian Shan that prevent the transport of moisture, rainfall is reduced, especially in January and February (Aizen et al, 1995(Aizen et al, , 2001.…”
Section: Study Areamentioning
confidence: 99%
“…Paleoenvironmental studies from Kyrgyzstan indicate rather dry conditions during Phase II. Lauterbach et al (2014) reported a pronounced dry interval for Lake Son Kul between 4,950 and 3,900 cal a BP. In accordance, a stalagmite record from Uluu-2 Cave, ∼250 km west of Lake Chatyr Kol, also suggests dry conditions between 4,700 and 3,900 cal a BP (Wolff et al, 2017).…”
Section: Holocene Human and Mammal Presence In The Lake Chatyr Kol Camentioning
confidence: 99%
“…The midlatitude Westerlies bring moisture from the Aral-Caspian Basin, the Mediterranean, the Black Sea and the North Atlantic (Aizen et al, 2006;Lauterbach et al, 2014), while the Asian summer monsoon has only been of minor importance, at least since the midHolocene (Cheng et al, 2012). The Siberian High reaches south to the Tien Shan area and blocks the midlatitude Westerlies during winter, which results in low winter precipitation due to the dry air masses of the Siberian High (Aizen et al, 1995(Aizen et al, , 2001Ricketts et al, 2001).…”
Section: Changes In Precipitation/evaporationmentioning
confidence: 99%
“…As one of the driest areas in the world, southern Central Asia is undergoing the influence of different climatic systems at different space and time scales, but presently dominated by prevailing winds from the West, so-called 'westerlies' (Cheng et al 2012(Cheng et al , 2016Heinecke et al 2016;Lauterbach et al 2014;Wang et al 2010). It belongs to the desert climatic zones, with a semi-arid to arid climate, characterized by low rainfall from the end of fall to mid spring and by a maximum exposure to the sun and high temperatures the rest of the year (Mannig et al 2013).…”
Section: Short Note On the Geography Of Southern Central Asia And Normentioning
confidence: 99%
“…In central Asia, Palaeoclimate studies particularly investigated the relationships between the atmospheric circulation and high-mountain environments through alpine and subalpine lake records (Beer et al 2007;Heinecke et al 2016;Lauterbach et al 2014;Mischke et al 2010;Ricketts et al 2001). These studies infer the decrease of the influence of the Monsoon and the dominance of the Westerlies, bringing arid conditions during the second half of the Mid-Holocene to the present.…”
Section: The Palaeoclimate Datamentioning
confidence: 99%